Exploring ESP Students’ Perception toward the Potential of Artificial Intelligence to Promote Students’ Self-Efficacy in English Writing Skill - Silvia Nanda Putri Erito (English Language Education Department, Universitas Majalengka, 2023)
This study aimed to explain ESP (English for Specific Purposes) students’ perception toward the potential of AI to promote their self-efficacy in their English writing skill by examining its impact on students’ learning experiences and perceptions. The present investigation employed a qualitative case study. The data collected by open-ended questionnaire in online form distributed to forty students in accounting major. The findings showed that the students positively perceived toward the potential of AI to promote students’ self-efficacy in their English writing skill, they believed that AI play important role and impact their self-efficacy, enhance their motivation, reduce their anxiety, give easy access to the students to get feedback quickly with better recommendation of writing and provide interactive learning in achieving consistency in student’ English writing skill.